Evidences of Citizens' Engagement from COVID-19 Pandemic in Italy. Health Care System' Facebook Communication. Issue 3 (17th February 2023) - Mori, Elisa; Barabaschi, Barbara; Cantoni, Franca; Virtuani, Roberta
ABSTRACT: The study aims at demonstrating how social communication has changed in terms of flows and content during the COVID-19 pandemic to get to the fact that health system organizations have embarked on a path of rapprochement with the citizen that starts from the methods of communication and interaction. This article presents an exploratory and multidisciplinary study conducted through the analysis of the Facebook page of the Italian Local Health Units (LHUs) site in the areas with the highest cumulative COVID-19-induced mortality rate. The study affirms that they are in an early stage of the process both for the acquisition of skills for social communication and for the definition of a communication strategy.